Finns det ett samband mellan upplevd stress och arbetsminne? En kvantitativ studie bland studenter vid Lunds universitet. - Åström,Sofia; Ekstrand,Tess (2026)
The present study investigates the relation between perceived stress and working among university students at Lund University and if there are any clear gender differences in perceived stress. The study was designed with a within-group design and was conducted online via a web-based questionnaire that measured perceived stress and a working memory test. Standardized measures were used for stress, the Perceived Stress Scale (PSS-10) and for working memory, the Reversed Digit Span task. The relationship between stress and working memory was analyzed using a multiple regression analysis and gender differences in perceived stress were examined using an independent t-test. The results showed no statistically significant relationship between perceived stress and working memory. Which means that stress levels explained only a very small proportion of the variance in working memory performance. Furthermore the results revealed no statistically significant difference in perceived stress between the different genders. Thus, the study found no evidence that stress affects working memory or differs between genders among university students at Lund University.
Keywords: Stress; arbetsminne; könsskillnader; Perceived Stress Scale-10; Reversed Digit Span